Demographics, treatment patterns, safety, and real-world effectiveness in patients aged 70 years and over with chronic lymphocytic leukemia receiving bendamustine with or without rituximab: a retrospective study. (June 2013) - Kolibaba, Kathryn S.; Sterchele, James A.; Joshi, Avani D.; Forsyth, Michael; Alwon, Erin; Beygi, Hooman; Kennealey, Gerard T.
Objectives: Bendamustine is a unique cytotoxic agent active against various human malignancies, including chronic lymphocytic leukemia (CLL). In vitro studies suggest that cytotoxic activity of bendamustine on CLL-derived cells is synergized by rituximab. A retrospective chart review was conducted to characterize treatment-naïve outpatients and those with relapsed disease aged 70 years and over with CLL receiving bendamustine (with or without rituximab) and to evaluate real-world patterns of care, safety, and effectiveness. Methods: Using McKesson Specialty Care/US Oncology Network iKnowMed databases, 91 outpatients with at least two recorded visits and at least two cycles of bendamustine monotherapy or bendamustine–rituximab combination therapy were identified and included. Mean age at diagnosis and start of first therapy was 70.3 and 77.4 years respectively, and 63.7% of patients were men. Results: Observed overall response rate was 56.3% in pooled treatment-naïve patients [ n = 9; complete response (CR) 18.8%; partial response (PR) 37.5%; nodular partial response (nPR) 0%] and 58.7% in pooled patients with relapsed disease ( n = 44; CR 13.3%; PR 44.0%; nPR 1.3%). Median time to progressive disease has not been reached for the 16 treatment-naïve patients (median follow up 15.1 months), and was 18.4 months for those with relapsed disease ( n = 73). No unexpected toxicities were observed. Overall rate of blood/bone marrow toxicities (all grades) was 40.7%; grade 3/4 rates were 18.8% in treatment-naïve patients and 25.3% in those with relapsed disease. Most frequent nonhematologic adverse events were fatigue and rash. Conclusion: In this retrospective chart review of 91 outpatients with CLL aged 70 years and over, bendamustine (with or without rituximab) was an effective therapeutic option with manageable toxicity.